Efficacy and Safety of Complementary Therapy With Jing Si Herbal Tea in Patients With Mild-To-Moderate COVID-19: A Prospective Cohort Study - Hsieh, Po-Chun; Chao, You-Chen; Tsai, Kuo-Wang; Li, Chung-Hsien; Tzeng, I-Shiang; Wu, Yao-Kuang; Shih, Cheng Yen (Frontiers in Nutrition, 2022)
Background: Since late 2019, there has been a global COVID-19 pandemic. To preserve medical capacity and decrease adverse health effects, preventing the progression of COVID-19 to severe status is essential. Jing-Si Herbal Tea (JSHT), a novel traditional Chinese medicine formula was developed to treat COVID-19. This study examined the clinical efficacy and safety of JSHT in patients with mild-to-moderate COVID-19. Methods: In this prospective cohort study, we enrolled 260 patients with mild-to-moderate COVID-19. The enrolled patients were divided into the JSHT (n = 117) and control (n = 143) groups. Both groups received standard management. The JSHT group was treated with JSHT as a complementary therapy. Results: Compared with standard management alone, JSHT combined with standard management more effectively improved the reverse transcription–polymerase chain reaction cycle threshold value, C-reactive protein level, and Brixia score in the adult patients with mild-to-moderate COVID-19, especially in the male and older patients (those aged ≥60 years). The results revealed that the patients treated with JSHT combined with standard management had 51%, 70%, and 100% lower risks of intubation, Medisave Care Unit admission, and mortality compared with those receiving standard management only. Conclusions: JSHT combined with standard management more effectively reduced the SARS-CoV-2 viral load and systemic inflammation and alleviated lung infiltrates in the patients with mild-to-moderate COVID-19, especially in the male and older patients (those aged ≥60 years). JSHT combined with standard management may prevent critical status and mortality in patients with mild-to-moderate COVID-19. JSHT is a promising complementary therapy for patients with mild-to-moderate COVID-19.